Impact of Diet Supplementation and Age at Slaughter on Carcass Characteristics of Creole Goats - Bambou, Jean-Christophe; Cériac, Steve; Liméa, Léticia; Arquet, Rémy; Bocage, Bruno; Alexandre, Gisèle (Frontiers in Veterinary Science, 2021)
The objective of this study was to evaluate the effects of diet and age on finishing performances and carcass characteristics of male Creole goats. A total of 91 weaned male Creole kids (84 days-old ±7 days, 9.2 kg live weight (LW) ±0.5 kg) were randomly allocated in a 2×3 experimental design. The animals were fed individually with 2 diets: C0: a 28-day old Digitaria decubens grass alone, or C50: the same grass plus a commercial concentrate (50% of the total diet) then slaughtered at 7, 11 or 15 months of age. Significant feeding regimen and age at slaughter effects were observed on the goat carcasses characteristics. The addition of concentrate improved the average daily gain (ADG), the dressing percentage and the conformation score (1-5 scale) from 46 to 88 g/day, 52.8 to 62.4% and 2.2 to 4.9, respectively. Moreover, carcasses of the C0 group appeared lean with less developed fat than the C50 group and lighter than visceral fat. The meat color was significantly more affected by the diet than the age. Our data suggested that the production of heavy carcasses with low proportions of fat in the meat is possible in this local breed. The valorisation of such a forage feeding system until 11 months of age or with the addition of concentrate from 7 to 11 months of age should be evaluated economically.